Pablo Neruda, A basic anthology. Edited by Robert Pring-Mill. Dolphin Books, Oxford, 1975; lxxxi + 218 pp. - Lasarte, Francisco (El Colegio de México, 1978)
Se reseñó el libro: A basic anthology. Edited by Robert Pring-Mill.